Wallacean shortfall: new records of Triplocania Roesler, 1940 (Psocodea: ‘Psocoptera’: Ptiloneuridae) for Brazil - Pereira, Antoniel F.; Boldrini, Rafael; Cutrim, Marcelo; Silva-Neto, Alberto M. (Entomological Communications, 2022)
Triplocania Roesler, 1940 has a high rate of endemism per country, with only five species out of a total of 118 described species, occurring in more than one country. Brazil is the second most diverse country in terms of Triplocania species, with 34 species recorded. In this paper, Triplocania furcatoides González-Obando, Carrejo-Gironza & García Aldrete, 2017 was recorded for Brazil and new records of Triplocania furcata New, 1972 made for four Brazilian states (Amazonas, Pará, Roraima and Tocantins), thus decreasing Wallace shortfall of these two species.